Evaluation of an Intervention to Improve Essential Obstetric and Newborn Care Access and Quality in Cotopaxi, Ecuador - Broughton, Edward; Hermida, Jorge; Hill, Kathleen; Sloan, Nancy; Chavez, Mario; Gonzalez, Daniel; Freire, Juana Maria; Gudino, Ximena (Frontiers in Public Health, 2016)
Background Despite improvements in health care utilization, disadvantages persist among rural, less educated and indigenous populations in Ecuador. The USAID-funded Cotopaxi Project created a provincial-level network of health services, including community agents to improve access, quality and coordination of essential obstetric and newborn care. We evaluated changes in participating facilities compared to non-participating controls. Methods The 21 poorest parishes (third-level administrative unit) in Cotopaxi were targeted from 2010-2013 for a collaborative health system performance improvement. The intervention included service reorganization, integration of traditional birth attendants with formal supervision, community outreach and education, and health worker technical training. Baseline (n=462) and end-line (n=412) household surveys assessed access, quality and use of care and women's knowledge and practices. Traditional birth attendants’ knowledge and skills were assessed from simulations. Chart audits were used to assess facility obstetric and newborn care quality. Provincial government data were used for change in neonatal mortality between intervention and non-intervention parishes using weighted linear regression. Results The percentage of women receiving a post-natal visit within first 2 days of delivery increased from 53% to 81% in the intervention group and from 70% to 90% in the comparison group (p≤0.001). Postpartum/counseling on newborn care increased 18% in the intervention compared with 5% in the comparison group (p≤0.001). The project increased community and facility care quality and improved mothers’ health knowledge. Intervention parishes experienced a nearly continual decline in newborn mortality between 2009 and 2012 compared with an increase in control parishes (p≤0.001). Conclusions The project established a comprehensive coordinated provincial-level network of health services and strengthened links between community, primary and hospital health care. This improved access to, quality, use and provision of essential obstetric and neonatal care and survival. Ecuador’s Ministry of Health is scaling up the model nationally.